Serological profile and hemolytic disease in term neonates with ABO incompatibility - Desiana Dharmayani; Djajadiman Gatot; Rinawati Rohsiswatmo; Bambang Tridjaja (Indonesian Pediatric Society, 2009)
Background Hemolytic disease of the newborn (HDN) due toABO blood type incompatibility is one of the most commoncause of neonatal hyperbilirubunemia that potentially leads tobilirubin encephalopathy. Data on ABO-hemolytic disease of thenewborn (ABO-HDN), especially regarding umbilical cord bloodserological profile, are limited.Objective To identify the serological profile and hemolytic disease in term neonates with ABO incompatibility.Methods This was a cross-sectional descriptive study, conductedat RSIA Budi Kemuliaan Jakarta.Results We found 68 healthy term neonates with ABOincompatibility, nine of them had positive direct antiglobulintest (OAT) result, and 38 subjects had a positive result onOAT with elution method. The highest titer of IgG was 1:8.Hyperbilirubinemia was found in 30 ( 44%) subjects, andABO-HDN was diagnosed in 28 (41 %) subjects. Within thepositive OAT group, eight out of nine subjects had sufferedfrom hyperbilirubinemia and ABO-HDN. Meanwhile, withinthe positive OAT with elution method group; 24 subjects hadsuffered from hyperbilirubinemia with 23 of them having ABOHDN. Based on the chi-square analysis; those with positive OAT with elution method had 3.2 times higher risk of suffering from ABO-HDN. Furthermore, there was a 3.6 times higher risk ofsufferring from hyperbilirubinemia.Conclusion In healthy term neonates with ABO incompatibility,the incidence of ABO-HDN is 41%. OAT serological examinationwith elution method is better than OAT in assessing riskfor hyperbilirubinemia and ABO-HDN.